The multinational corporations and Brazil : the impact of multinational corporations in the contemporary Brazilian economy - Arruda, Marcos (Brazilian Studies, Latin America Research Unit, 1975)
The "Brazilian model" of development has been hailed by development economists. The "Brazilian miracle" characterized by a rapid rise in gross national product, has been the envy of the so-called developing world....